Settings for Health Promotion : Linking Theory and Practice. - Poland, Dr. Blake D. D. (SAGE Publications, 1999)
This book is the first full-length in-depth treatment of settings as a focal point for planning, organizing and implementing health promotion. The concept of 'setting' is fundamental to theory and practice in health promotion. Internationally renowned authors describe the state-of-the-art in the theory and practice of health promotion in settings such as the home, school, workplace, community, and state and offer insightful commentaries on each other's work.